Insights into the impact of a membrane-anchoring moiety on the biological activities of bivalent compounds as potential neuroprotectants for Alzheimer’s disease - He, Liu (J Med Chem, 2018)
Bivalent compounds anchoring in different manners to the membrane were designed and biologically characterized to understand the contribution of the anchor moiety to their biological activity as neuroprotectants for Alzheimer’s disease. Our results established that the anchor moiety is essential and we identified a preference for diosgenin, as evidenced by 17MD. Studies in primary neurons and mouse brain mitochondria also identified 17MD as exhibiting activity on neuritic outgrowth and the state 3 oxidative rate of glutamate while preserving the coupling capacity of the mitochondria. Significantly, our studies demonstrated that the integrated bivalent structure is essential to the observed biological activities. Further studies employing bivalent compounds as probes in a model membrane also revealed the influence of the anchor moiety on how they interact with the membrane. Collectively, our results suggest diosgenin to be an optimal anchor moiety, providing bivalent compounds with promising pharmacology that have potential applications for Alzheimer’s disease.